Strong and Reversible Covalent Double Network Hydrogel Based on Force‐Coupled Enzymatic Reactions. (28th April 2022) - He, Guangxiao; Lei, Hai; Sun, Wenxu; Gu, Jie; Yu, Wenting; Zhang, Di; Chen, Huiyan; Li, Ying; Qin, Meng; Xue, Bin; Wang, Wei; Cao, Yi
Abstract: Biological load‐bearing tissues are strong, tough, and recoverable under periodic mechanical loads. However, such features have rarely been achieved simultaneously in the same synthetic hydrogels. Here, we use a force‐coupled enzymatic reaction to tune a strong covalent peptide linkage to a reversible bond. Based on this concept we engineered double network hydrogels that combine high mechanical strength and reversible mechanical recovery in the same hydrogels. Specifically, we found that a peptide ligase, sortase A, can promote the proteolysis of peptides under force. The peptide bond can be re‐ligated by the same enzyme in the absence of force. This allows the sacrificial network in the double‐network hydrogels to be ruptured and rebuilt reversibly. Our results demonstrate a general approach for precisely controlling the mechanical and dynamic properties of hydrogels at the molecular level. Abstract : A force‐coupled enzymatic reaction was used to tune a strong covalent peptide linkage to create a reversible bond and engineer double network (DN) hydrogels that combine high mechanical strength and reversible mechanical recovery. The peptide ligase, sortase A (SrtA), can promote the proteolysis of peptides under force and re‐ligation of peptides without force, allowing the sacrificial network in DN hydrogels to be ruptured and rebuilt reversibly.